Studi Bibliografi: Perkembangan Penelitian Kebijakan Dividen Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Fathony, Haris Reza; Aryani, Y. Anni; Setiawan, Doddy; Djuminah, Djuminah (Jurnal Akuntansi dan Bisnis, 2024)
This study aims at providing empirical evidence of research-development on dividend policy in Indonesia Stock Exchange. This study analyzes the dividend policy which consists of 32 articles from 19 nationally accredited journal (Sinta 1 and Sinta 2) taken from 2017 until 2022. The writers of this study do the classification based on the topic, finance variable and non finance variable. The method used in this study is "Charting The Field. " It is found that ROA gives inconsistent impact on dividend policy. Non finance variable, company age and institutional ownership are inconsistent as well. The model of anteseden variable from finance variable and non finance variable use additive model more frequently upon dividend policy. Then, based on consequence variable, it is found that dividend policy has a relation with company value, stock price, earnings smoothing, debt policy leverage, ROA and individual ownership. This implies that dividend policy is used by the management to make a decision in distributing dividends or they are not distributed in the form of retained earnings. There are still many inconsistencies about the result of this kind of research. So, the topic about dividend policy is still being researched by others who are interested in it.